English Teacher’s Perceptions on Interactive Multimedia and Differentiated Learning in Banda Aceh - Jannah, Miftahul; Fitri, Zahratul; Ayouni, Nour; Tinambunan, Intan Surur (International Journal of Education, Language, and Religion, 2025)
This study aims to analyze the perceptions of high school English teachers in Banda Aceh regarding interactive multimedia learning and differentiated instruction, using a mixed-methods approach that combines quantitative data (questionnaires) and qualitative data (interviews) to explore teachers' perceptions, experiences, and challenges more comprehensively. The data were analyzed using descriptive statistical and thematic analysis. A total of 40 high school English teachers, members of the English Language Educators in Aceh (ELEA) community, were selected as respondents using purposive sampling. The results indicate that teachers hold highly positive perceptions of interactive multimedia learning, particularly in terms of student motivation, creativity, and learning engagement. For differentiated instruction, teachers found this method effective in improving learning outcomes and task flexibility. Recommendations from the study include enhancing technological infrastructure, providing regular training, and fostering collaboration among teachers to optimize the implementation of both methods. These findings underscore the importance of technical support and professional development for teachers to maximize the impact of technology-based and differentiated learning in the classroom.